HUBUNGAN ANTARA KONSUMSI ASAM LEMAK OMEGA-3 TERHADAP GEJALA OSTEOARTHRITIS PADA LANSIA - Arya Cetta Dewangga Buana; Nuryani Sidarta (Fakultas Kedokteran Universitas Trisakti, 2026)
Osteoarthritis is a degenerative joint disease commonly affecting older adults and causing chronic pain and reduced physical function. Omega-3 fatty acids have anti-inflammatory properties that may influence inflammatory processes in osteoarthritis. This study aimed to describe omega-3 fatty acid intake and changes in osteoarthritis symptoms among older adults using a longitudinal design. This study was conducted at Ciawi Regional General Hospital (RSUD Ciawi) and involved 52 older adults aged ≥60 years with diagnosed osteoarthritis. Exclusion criteria included obesity (BMI >25 kg/m²), use of analgesic medications, and a history of joint trauma. Omega-3 intake was assessed using a Food Frequency Questionnaire (FFQ) over six weeks, while osteoarthritis symptoms were evaluated using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Data were analyzed using the Wilcoxon signed-rank test. All respondents had low omega-3 fatty acid intake. The highest WOMAC scores were observed in the physical function domain related to heavy activities (73.07%). Based on WOMAC scores, 67.3% of respondents had severe pain and 32.69% had moderate pain. A statistically significant change in WOMAC scores was found, with 23 respondents showing a reduction in scores after the observation period.